A geometric characterization of Powell-Sabin triangulations allowing the construction of C2 quartic splines. (15th October 2021) - Barrera, D.; Eddargani, S.; Ibáñez, M.J.; Lamnii, A.
Abstract: The paper deals with the characterization of Powell-Sabin triangulations allowing the construction of bivariate quartic splines of class C 2 . The result is established by relating the triangle and edge split points provided by the refinement of each triangle. For a triangulation fulfilling the characterization obtained, a normalized representation of the splines in the C 2 space is given.